Developing Fairy Tale Book of Mbojo Tribe in Two Languages as a Teaching Materials of Indonesian Language for Increasing Students' Achievement - Arif Bulan; Hasan Hasan (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2020)
This research was motivated by the fact that local tales are not well documented. So that implies the limitations of the local fairy tale book archives that can be used as effective teaching materials in increasing learning achievement. This development research aimed to: (1) produce feasibility of fairy tale book of the Mbojo tribe for the fourth-grade students of  SDN 26 Dompu, (2) to determine the effectiveness of the fairy tale book of the Mbojo tribe in improving the learning achievement of the fourth-grade students of SDN 26 Dompu. This research was development research (R & D) using the ADDIE model (analysis, design, development, implementation, and evaluation). The results of this research: (1) The fairy tale book of the Mbojo tribe in two languages as teaching material for Indonesian to improve students achievement was feasible to be tested and used. Feasibility was obtained from the assessment of the expert of media and materials; (2) The fairy tale book of the Mbojo tribe in two languages as Indonesian language teaching materials to improve student achievement was effective in increasing student achievement. The effectiveness was seen from the results obtained by students. The test results showed that the students were able to pass the minimum completeness criteria score set by the school.